The effect of a 12-week custom foot orthotic intervention on muscle size and muscle activity of the intrinsic foot muscle of young adults during gait termination. (August 2020) - Protopapas, Katrina; Perry, Stephen D.
Abstract: Background: The tissue stress theory is commonly used to prescribe foot orthoses, however the mechanisms of foot orthoses are not understood well. The effect foot orthotics have on the plantar intrinsic muscles remains unclear. The study was designed to assess changes in muscle size and activity of the intrinsic muscles of individuals with pes planus after wearing custom-made foot orthotics for 12-weeks. Methods: Eighteen young adults with pes planus were allocated by stratified sampling into the orthotic group ( n  = 9) or control group (n = 9). Ultrasonography measured the cross-sectional area of the flexor digitorum brevis, abductor digiti minimi, and abductor hallucis at baseline, 6 and 12-weeks. Subsequently, participants completed an unexpected gait termination protocol (12 of 50 trials unexpected) and average electromyography magnitude was recorded. Findings: After 12-weeks the orthotic group cross-sectional area significantly decreased by 9.6% ( P  < .001) for the flexor digitorum brevis, 17.1% for abductor digiti minimi ( P  < .001) and 17.4% for abductor hallucis ( P  < .001). There were no significant differences of muscle activity magnitude for the intrinsic muscles. Interpretation: The short-term use of custom-made foot orthoses created a decrease in muscle size of the flexor digitorium brevis, abductor digiti minimi and abductor hallucis plantar intrinsic muscles but had no effect on muscle activity. Clinically, these results help to understand the adaptations that are created when foot orthoses are supporting a pes planus foot structure when reducing plantar pressures. These findings may help enhance the prescription of foot orthoses by adding a strength program to prevent disuse atrophy of these muscles. Highlights: Wearing custom foot orthoses reduced the size of the plantar intrinsic foot muscles. The foot intrinsic muscle activity remained the same post orthoses utilization. Disuse atrophy had no effect on participants ability to terminate gait unexpectedly.